Mental toughness and attributions of failure in high performing male and female swimmers - Meggs, J.; Chen, M. A. (Journal of Human Sport & Exercise, 2018)
This study examined the reciprocal relationship between mental toughness and failure attributions in high level swimmers. Participants were 80 (male (n=44) and female (n=36) Mage=21.64, S.D: 4.96 years) regional and national level swimmers who were currently competing. Participants were asked to recall a perceived failure in the previous four weeks, fill in the CSGU attribution measure and eight weeks later complete a MTQ48 measure of mental toughness. Stepwise regression analysis, found a strong reciprocal relationship between mental toughness and controllability. When the generalizability dimensions were added to the model, stepwise regression found a significant effect of controllability and universality on mental toughness (DeltaR2 = 0.035, p = 0.036) and for mental toughness and stability on controllability (DeltaR2 = 0.042, p = 0.021). Separate stepwise analysis for both genders, revealed that males mental toughness and stability predicted controllability (DeltaR2 = 0.200, p = 0.029) and females mental toughness and universality (DeltaR2 = 0.080, p = 0.027) predicted controllability. In conclusion the present study found evidence for a reciprocal relationship between controllability and mental toughness following failure for a group of high level male and female swimmers. There was gender differences in how the generalizability dimensions predicting controllability. Findings are discussed in terms of mental toughness and attributions being reciprocally related in response to competitive failure.